Archaeological Identification and Cultural Significance of Sorawolio II Fort in Bukit Wolio Indah, Baubau City - Abdul Alim; Siti Nurul Hidayah M (Journal of Law, Social Science and Management, 2025)
Background: Fortresses are cultural heritages that hold significant historical and archaeological value, as they reflect the social, political, and military dynamics of the past. Baubau City, known for its rich historical legacy, preserves numerous sites that remain underexplored, including Sorawolio II Fort, located to the east of the Buton Palace Fortress. Objectives: This study aims to identify the archaeological remains at the Sorawolio II Fort site and to analyze the function of the fort based on physical evidence discovered on-site. Methods: The research employs a qualitative descriptive approach using the Theory of Archaeological Space as the analytical framework. Data were collected through field observation, documentation, and literature review. Results: The findings indicate that Sorawolio II Fort features two bastions, five windows, and 26 observation holes distributed along the fort walls. Additionally, six cannons were discovered, supporting the hypothesis that the fort served a defensive purpose. Conclusion: Sorawolio II Fort functioned as a defensive and security structure, as evidenced by its architectural elements and archaeological artifacts. This study underscores the importance of preserving historical remains in Baubau City. Keywords: Sorawolio II Fort, archaeological space, historical remains, defense, Baubau City, bastion, cannon